Strategi Pengembangan Wisata Bahari Di Desa Taluak Kota Pariaman - Agung Azharun Ridwan; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2023)
The aims of this research are (1) to find out what the Marine Tourism Development Strategy is in Taluak Village, Pariaman City, (2) to identify obstacles and efforts in developing marine tourism in Taluak Village, Pariaman City. This type of research is descriptive qualitative using the 6A main component theory of tourism development and SWOT analysis techniques. The research was conducted in Taluak Village, Pariaman City, the objects of which were the beaches in Taluak Village, namely Kata Beach, Ma'ruf Amin Beach and Karan Beach. The results of this research show that marine tourism in Taluak Village is managed by two different parties, namely the Pariaman City Government manages Kata Beach and the Taluak Village Government manages Ma'ruf Amin Beach and Karan Beach. Kata Beach, which is managed by the city government, has shown all the main components of tourism development, but Ma'ruf Amin Beach and Karan Beach, which are managed by the village government, have not shown all the main components of tourism development.